ANALISIS FAKTOR KOMUNIKASI TERHADAP PENGAMBILAN KEPUTUSAN PADA KECAMATAN TANJUNGBALAI UTARA - Gunawan Adiputra Munthe; Wulan Wardaningtias Putrini; Nurmala Siregar; Riski Anggita Akbar Sagala; Nur Ainun harahap (Universitas Islam Sumatera Utara, 2021)
This research discusses about the influences of perception, emotion, and knowledge as communication factors on decision making at North Tanjungbalai District. The aim of this research is to analyse the influences of perception, emotion, and knowledge both partially and simultaneously on decision making at the office. This is a quantitative research with random sampling technique. The sample is 44 employees. Results show that each independent variable; perception, emotion, and knowledge, partially influences decision making positively and significantly. perception has tcount value 2,578 and level of significance 0.016, emotion has 3,200 and 0.004, and knowledge has 4,201 and 0.000. Simultaneously, perception, emotion, and knowledge have significant and positive influences on decision making at North Tanjungbalai District with Fcount value 19,355 and level of significance 0.000.